Chapter 8 Trading in spiritual and earthly good Franciscans in semi-rural Palestine - Tramontana, Felicita (Religious Cultures in the Early Modern World, 2020)
The spread of Catholicism among the local Christian population in the Syro-Palestinian region has attracted the attention of many scholars. Previous research has described how missionaries' work was facilitated by the patronage of local notables, by the establishment of personal ties with locals, and more generally by a wide range of daily interactions, such as providing medical assistance. 1 In this framework, academic attention has mostly focused on the cities, consistent with the fact that missions were far more numerous in urban areas. An important exception is a pioneering work by Bernard Heyberger. This early study reconstructs how, departing from their houses in cities such as Sayda and Tripoli, Jesuits and Capuchins visited rural villages in Galilee and Lebanon. Inspired by the model of rural missions developed in Europe during the Catholic Reformation, their activities hinged on confession and preaching. In line with the regional framework, missionaries also carefully built ties with locals and offered their medical competencies, which greatly helped their cause. 2 Although the importance of interactions with the locals in the spread of Catholicism in the Middle East has been widely acknowledged, many questions about the nature of these interactions still remain unanswered: How did the administrative and economic system that characterized rural and semi-rural spaces influence missionaries' interactions with the surrounding areas? What was the relationship between missionaries' entanglement with local society and their evangelizing activities? And, finally, to what extent did these interactions turn the missionaries into "localized" protagonists?